Outing Class sebagai Inovasi Pendistribusian Santunan Anak Yatim dan Dhuafa oleh Lazis Al-Haromain Kediri - Zuraidah Zuraidah; Refina Cahya Ning Pangisti; Sefia Firgi Andani; Irsa Dwi Avira Wati; Rani Nabilahsari (Universitas 45 Surabaya, 2025)
This study explores the innovation in distributing charitable aid to orphans and underprivileged children through an outing class activity organized by LAZ Al Haromain. The outing class, held by the Al-Hikmah Qur'anic Education Park in Pelem Village, Pare District, took place at Tirto Tani Djojo Tourism Site in Tiru Lor Village, Gurah District, and was facilitated by the Al-Haromain charity and zakat institution in Kediri. The purpose of this study is to understand the extent to which combining charitable distribution with educational outdoor activities can positively impact beneficiaries. A descriptive qualitative approach was employed to analyze participants' experiences, perceived benefits, and the effectiveness of the program in enhancing the psychological and social well-being of recipient children. The findings indicate that aid distributed through educational activities (outing classes) can enhance learning motivation, self-confidence, and social skills among participants. Moreover, this method is considered more effective than conventional distribution models, as it creates more meaningful experiences and fosters stronger emotional engagement between donors and recipients. In conclusion, this approach adds significant value for beneficiaries and can serve as a more innovative and sustainable model for social aid distribution.